Drug Utilization Study in Patients Attending Hypertension Clinic of a Tertiary Care Hospital, Rajasthan, India - Dherendra SHARMA; Sunil GOYAL; Arvind SINGH; Bhoomika SHARMA; Mayur GANDHI; Amit BHIMAWAT; Archana JAIN; Amit GUPTA; Shivankan KAKKAR (Modern Medicine)
Background: Hypertension is a major public health problem in India, affecting a significant proportion of the population. Drug utilization research is important for assessing the rationality of drug treatment and for identifying areas for improvement. This study examined the drug utilization pattern of antihypertensive drugs in hypertensive patients at an Outpatient Department (OPD) in Udaipur, Rajasthan, India, based on JNC-8 classification. Materials and Methods: The observational cross-sectional study included 300 hypertension patients aged above 25 attending the hypertension clinic. Exclusions were made for inpatients, age < 25, uncertain diagnosis, pregnant/lactating mothers, and patients subsequently admitted after OPD visits. Results: The majority of affected patients were above 60 years old, with most having hypertension for 2-5 years, often accompanied by Type II Diabetes Mellitus. Oral administration was the primary drug delivery route. On average, patients received 1.93 antihypertensive drugs per encounter (range: 1 to 4), with an average of 5.82 drugs per encounter (range: 1 to 12). Losartan (72%) and amlodipine (46%) were the most prescribed drugs, with Angiotensin Receptor Blockers (ARBs) being the most prescribed drug class (79.3%), followed by Calcium Channel Blockers (CCBs) at 46.6%. The most common therapy was a two-drug combination (44.6%), followed by single-drug therapy (33%). Approximately 26.3% of prescriptions indicated potential drug interactions. Conclusions: This study provides valuable baseline data on the prescribing pattern of antihypertensive drugs. Rational prescribing practices are being followed, with the majority of patients being prescribed a combination of two or three antihypertensive drugs. However, there is a need to educate patients about the risks associated with uncontrolled high blood pressure and the benefits of lifestyle changes.